SUSTAINABILITY OF ENVIRONMENTAL INDICATORS FOR THE METROPOLITAN REGION OF SAO PAULO - Toni Junior, Claudio Noel l de [UNESP] (Pontificia Univ Catolica Sao Paulo-puc-sp, 2016)
This research aims to bring the concept of cities in the metropolitan region of Sao Paulo (MASP) through the creation of the Sustainability Index of the Metropolitan Region of Sao Paulo (ISRMSP) through data from institutions like the United Nations Program for Development Program (UNDP), an agency of the United Nations (UN) through the Atlas of Human Development of cities and the Municipal Human Development Index (HDI - M) combine the index to be created in two aspects : the HDI - M program and the City of Green City Blue ( PMVA) through the Environmental Assessment Index (WAI) from the Department of Environment of the State of Sao Paulo, which has as attribution develop existing infrastructure in cities, through the advancement and improvement of technical progress through Science, Technology and information to modify an existing structure to optimize production processes in various variables such as housing, electricity, drinking water so that there is well-being and quality of life for society. The survey included the cities of MRSP to portray what can be improved in relation to education at the expense of social and environmental indicators. Through the use of geotechnology, as the program Arcgis 10.1, thematic maps will be prepared for these Brazilian cities, with the objective of addressing the multiple variables that demonstrate the dynamics of sustainability and quality of life.
Keywords: Urbanization; environmental; sustainability indicators